2018
DOI: 10.1002/anie.201806800
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Molecular Aggregation States to Realize Polymorphism, AIE, MCL, and TADF in a Single Molecule

Abstract: Multifunctional emitting materials are scarce and need to be further explored. Now, a newly anthraquinone derivative, 2-(phenothiazine-10-yl)-anthraquinone (PTZ-AQ) was designed and synthesized and found to demonstrate polymorphism, multi-color emission, aggregation-induced emission (AIE), mechanochromic luminescence (MCL), and thermally activated delayed fluorescence (TADF) in its different solid forms. It is shown for the first time that TADF properties of a compound can be systematically tuned via its aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 193 publications
(101 citation statements)
references
References 57 publications
1
98
1
1
Order By: Relevance
“…Lee et al. reported a rather intriguing molecule with AIE and TADF properties that also showed polymorphism and mechanochromic luminescence (MCL) phenomenon within the individual molecule . Five different aggregation states were found, including three different crystal structures.…”
Section: Tadf Molecular Design Towards Efficient Oleds With Superior mentioning
confidence: 99%
“…Lee et al. reported a rather intriguing molecule with AIE and TADF properties that also showed polymorphism and mechanochromic luminescence (MCL) phenomenon within the individual molecule . Five different aggregation states were found, including three different crystal structures.…”
Section: Tadf Molecular Design Towards Efficient Oleds With Superior mentioning
confidence: 99%
“…More recently,L ee andc o-workers reported that as imilarD -Ac ompound, PTZ-AQ,w hich contained phenothiazine as a donor, showed multifunctional properties of AIDF,p olymorphism, andamechano-inducedl uminescence color change (Figure 29 a). [105] Depending on the crystallizationc onditions, PTZ-AQ could adopt up to fived ifferentp olymorphs with three different emission colors, yellow (l em = 545, 554 nm), orange (l em = 568 nm;O -crystal), and red (l em = 606,6 49 nm), and various F PL values within the range 0.02-0.84 (Figure29b). Amongt he different polymorphs, the R-crystal showed distinct TADF properties, with av ery small DE ST value (10 meV) and a high F PL value (0.84).…”
Section: Tadf-active Materials That Exhibit Mechano-induced Emission-mentioning
confidence: 99%
“…Implementing the techniques found in the works mentioned above to TADF systems becomes somewhat more complicated as there is now not just the behavior of the prompt singlet emission to explain but also the processes and energetics underlying rISC and delayed emission. Functional phenomena in TADF systems as a result of intermolecular interactions have been observed for a range of D-A and D-A-D systems (Hladka et al, 2018;Huang et al, 2018;Klimash et al, 2018;Pashazadeh et al, 2018;Shi et al, 2018;Skuodis et al, 2018;Bhatia and Ray, 2019;Zheng et al, 2019). These works provide methodologies and insights in understanding the influence that intermolecular interactions have on TADF emitters including their photophysical properties.…”
Section: Novel Tadf Emitters Exhibiting Functional Behaviormentioning
confidence: 88%